The impact of digital economy on energy conservation and emission reduction: Evidence from prefecture-level cities in China - Cheng Zhang; Yirui Zhang; Hua Zhang; Jiaying You; Xinke Lv; Xinyu Cheng (Sustainable Futures)
In the face of global climate challenges and energy crises, China aimed to enhance energy conservation and emission reduction (ECER). This study explored the role of the digital economy in boosting energy efficiency and supporting sustainable development by constructing an index system, applying principal component analysis, and using spatial econometric models to assess the impact of digital economic development in China's prefecture-level cities on ECER. Findings revealed regional development disparities and complex spatial interactions that influence ECER. The digital economy showed potential to reduce emissions after reaching a particular scale, suggesting policy recommendations for balanced growth.